Mappadendang and the Politics of Religious Orthodoxy: Cultural Adaptation in Contemporary Bugis Society - Yaffa, Aurea Chiara; Firnanda, Deviyan Angel (Journal of Studies on Art, Culture and Society, 2025)
This study examines the transformation of Mappadendang, a traditional Bugis harvest ritual, amidst the rise of Islamic orthodoxy in contemporary Indonesia. Once a unifying cultural celebration, Mappadendang has experienced a decline in Muslim participation due to increasing scripturalist interpretations that view the ritual as incompatible with religious doctrine. Employing an ethnographic case-study approach in a South Sulawesi village, this research explores the community’s adaptive strategies, including ritual negotiation, symbolic reinterpretation, and religious reframing. The findings highlight how local actors maintain cultural resilience by transforming tradition into forms more acceptable to dominant religious norms. Through the frameworks of cultural politics and Islamic modernisation, the study underscores that cultural change in Muslim societies involves negotiation, not merely rejection, of heritage. This work contributes to broader discourses on religious orthodoxy, local identity, and the politics of cultural adaptation in plural societies.